2023
DOI: 10.3389/fpls.2023.1110727
|View full text |Cite
|
Sign up to set email alerts
|

Responses of dry matter accumulation and partitioning to drought and subsequent rewatering at different growth stages of maize in Northeast China

Abstract: IntroductionDry matter accumulation (DMA) and dry matter partitioning (DMP) are important physiological processes determining crop yield formation. Deep understanding of the DMA and DMP processes and their responses to drought are limited by difficulty in acquiring total root biomass.MethodsPot experiments with treatments quitting and ceasing ear growth (QC) and controlling soil water (WC) during vegetative (VP) and reproductive (RP) growth stages of maize (Zea mays) were conducted in Jinzhou in 2019 and 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…The tuber fresh weight, tuber volume, tuber number, and theoretical yield of certified seeds were all greater than those of the pre-elite seeds, except for the pre-elite seed of Chuanyu 117, which had a greater number of potatoes per plant than its certified seed. Analysis of variance (Table 4) and Duncan's multiple comparisons showed that tuber Dry matter accumulation is the basis for crop yield formation [22,23], and the dry matter accumulation balance period is a critical period when the potato growth center shifts from above ground to below ground [24]. The root system of potatoes is relatively small, and the root to crown ratio is relatively low [25].…”
Section: Differences In Theoretical Yield and Its Constituent Factors...mentioning
confidence: 99%
“…The tuber fresh weight, tuber volume, tuber number, and theoretical yield of certified seeds were all greater than those of the pre-elite seeds, except for the pre-elite seed of Chuanyu 117, which had a greater number of potatoes per plant than its certified seed. Analysis of variance (Table 4) and Duncan's multiple comparisons showed that tuber Dry matter accumulation is the basis for crop yield formation [22,23], and the dry matter accumulation balance period is a critical period when the potato growth center shifts from above ground to below ground [24]. The root system of potatoes is relatively small, and the root to crown ratio is relatively low [25].…”
Section: Differences In Theoretical Yield and Its Constituent Factors...mentioning
confidence: 99%
“…These detrimental effects primarily stem from the negative repercussions of heat stress on photosynthetic activity. Crop development exhibits a positive linear relationship with the net photosynthetic rate [3] influencing dry-matter accumulation [4] and allocation (biomass partitioning) [5,6]. The carbohydrate partitioning through photosynthesis results to constitute 60% of the total dry matter of the plant [7].…”
Section: Introductionmentioning
confidence: 99%